Revision of 1895. The General Ordinances of the City of Indianapolis. Containing also, Acts of the Indiana General Assembly so far as they Control Said City, to which Prefixed a Chronological Roster of Officers from, 1832 to 1895 and Rules Governing the Common Council Page 290-291, Image 372-373 (1895) - (:unkn) unknown (General Publisher, 1895)
Be it ordained by the Common Council and Board of Aldermen of the City of Indianapolis, That it shall hereafter be unlawful for any person to conduct or carry on any shooting gallery or room where rifle or pistol shooting is practiced, in the City of Indianapolis, without first having procured a license so to do, as hereinafter provided
--
Keywords: SHOOTING RANGES OR GALLERIES